METODE GERAK DAN LAGU UNTUK MENGENALKAN BAHASA INGGRIS PADA ANAK USIA DINI DI TK AISYIYAH BUSTANUL ATHFAL SINGARAJA: THE MOVEMENT AND SONG METHOD FOR INTRODUCING ENGLISH TO EARLY CHILDHOOD AT TK AISYIYAH BUSTANUL ATHFAL SINGARAJA - Marcelina, Putu Dian; Antara, Putu Aditya; Setyowahyudi, Rendy (Thufuli : Jurnal Ilmiah Pendidikan Islam Anak Usia Dini, 2023)
English language ability is important to have at this time. English language skills must be introduced from an early age. The purpose of this study was to find out the application of motion and song methods to introduce English to early childhood at Aisyiyah Bustanul Athfal Singaraja Kindergarten. The type of research used is a case study. The research subjects were teachers and principals at TK Aisyiyah Bustanul Athfal Singaraja. Methods of data collection using observation, interviews and documentation. Test the validity of the data using triangulation. Data analysis was performed using the Miles & Huberman model. The results obtained are the application of the movement and song method to introduce English to Aisyiyah Bustanul Athfal Kindergarten carried out in three stages, namely (1) planning when the teacher starts preparing equipment, songs and student lines, (2) implementation when the movements and songs begin to be carried out with teacher guidance and (3) closing/evaluation, namely when the teacher does a recall to find out changes in children’s English skills.